Exact tests and confidence sets for the tail coefficient of a-stable distributions - Jean-Marie Dufour; Jeong-Ryeol Kurz-Kim (Deutsche Bundesbank, 2003)
In this paper, using the Monte Carlo (MC) method we propose an estimation and (at the same time) a test procedure for the stability parameter of a-stable distributions. One powerful advantage of the MC method is that it provides an exact significance level for finite samples, whose distribution can be far different from that of asymptotic samples on which the level of confidence interval for estimates is usually based. Statistical theory for the MC method is given. A simulation study compares the efficiency of our estimate with the Hill estimate (Hill, 1975). Construction of significance level based on the MC method is exploited and the corresponding power function is also studied. An empirical application demonstrates an easy implementation of our estimation and test procedure. It turns out that our estimate can improve the efficiency of any estimator for a in terms of mean square error. – – In der vorliegenden Arbeit wird ein auf der Monte-Carlo-Methode basierendes Schätz- und Testverfahren für den Stabilitätsparameter von a-stabilen Verteilungen vorgeschlagen. Ein entscheidender Vorteil dieses Verfahrens liegt darin, dass es genauere Konfidenzintervalle für endliche Stichprobenumfänge angibt, die häufig von denen aus asymptotisch ermittelten Verteilungen abweichen. Die statistische Theorie für die Monte-Carlo-Methode wird abgeleitet. Anhand einer Simulationsuntersuchung wird die Effizienz von unserem Verfahren und dem Schätzverfahren von Hill (1975) verglichen. Es wird gezeigt, wie sich die Konfidenzintervalle durch die Monte- Carlo-Methode konstruieren lassen. Zudem werden die zugehörigen Gütefunktionen berechnet. Weiterhin zeigt ein empirisches Beispiel die Einfachheit der empirischen Implementierung unseres Verfahrens. Es wird deutlich, dass unser Verfahren die Effizienz beliebiger Schätzer für a im Sinne vom mittleren quadratischen Fehler verbessern kann.
Keywords: 330; Schätztheorie; Statistischer Test; Monte-Carlo-Methode; Theorie